2006
DOI: 10.1002/jso.20470
|View full text |Cite
|
Sign up to set email alerts
|

Modified intrapleural cisplatin treatment for lung cancer with positive pleural lavage cytology or malignant effusion

Abstract: We were able to perform this treatment for these advanced lung cancer patients, which had the preventive effect of carcinomatous pleuritis. This therapy shows the possibility of a treatment that might lead to an improvement in the prognosis of these patients, without causing severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…Reported pleural effusion response rates at 3 to 4 weeks range from 46 to 100%, depending on the agent. 15,[21][22][23][24][25][26][27][28][29] Because lung cancer accounts for approximately 50% of all MPEs, 5 we believe that docetaxel's efficacy in the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) may extend to the treatment of MPE as well. This phase I study was designed to determine the safety, feasibility, and pharmacokinetics of single-dose intrapleural administration of docetaxel for the treatment of MPEs.…”
mentioning
confidence: 99%
“…Reported pleural effusion response rates at 3 to 4 weeks range from 46 to 100%, depending on the agent. 15,[21][22][23][24][25][26][27][28][29] Because lung cancer accounts for approximately 50% of all MPEs, 5 we believe that docetaxel's efficacy in the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) may extend to the treatment of MPE as well. This phase I study was designed to determine the safety, feasibility, and pharmacokinetics of single-dose intrapleural administration of docetaxel for the treatment of MPEs.…”
mentioning
confidence: 99%
“…Muraoka et al also reported that intrapleural hypotonic cisplatin treatment had a preventive effect on carcinomatous pleuritis but had no survival benefit. 21 Satoh et al analyzed the recurrence patterns in patients with positive PLC results. They reported that 25 of 41 patients (72%) with recurrence had distant metastases, whereas pleural recurrence was observed only in 8 patients (25%).…”
Section: Discussionmentioning
confidence: 99%
“…In the present series, only seven patients underwent this therapeutic modality, but the clinical effect has been not evaluated because of the small number. Several investigators have reported the possible usefulness of intrapleural hypotonic cisplatin therapy during operation [6,15,16]. Satoh et al [6] emphasized that such local therapy may not be sufficient for prognosis improvement, but we think that a local therapeutic modality should be established as the first step for selected PLC-positive patients.…”
Section: Commentsmentioning
confidence: 92%